Sindrom Kindler - Budi Eko Prasetyorini; Suci Widhiati (PT Dexa Medica, 2023)
Kindler syndrome (KS) is a very rare form of epidermolysis bullosa (EB) and is a disease with defective FERMT1 gene. The FERMT1 gene provides the information needed to produce a protein called kindlin-1 where this protein plays an important role in attaching cells to the extracellular matrix which functions to hold, organize and connect cells in the body. Abnormalities in KS cause cells in the extracellular matrix to weaken so that the skin becomes brittle, prone to blisters and sores. Symptoms of SK are characterized by blisters that most often form on the backs of the hands and the tops of the feet, and thin, fragile skin. Mucosa of the eyes, intestines, esophagus, mouth, urinary tract and genitals may be affected. SK sufferers have a high sensitivity to light. Other symptoms can include discolored skin, thickened skin on the palms and soles and skin thatis atrophied or thin, dry and wrinkled. These symptoms appear in infancy and continue into adulthood, the risk of gingivitis (inflammation of the gums) which can lead to periodontitis or gum disease, throat, eye problems, higher risk of developing skin cancer and intestinal bleeding. Kindler syndrome management is basically preventive and symptomatic. Good wound care including the use of topical and systemic antibiotics for infected and ulcerated bullous lesions can reduce morbidity. Educating the patient to avoid trauma can help prevent blister formation.